HISTORICITY AND CONTEXTUALIZATION TO THE PROBLEMS OF MOSLEM AND NON-MOSLEM (A Hadith Study) - Assagaf, Ja`far (Al-Ulum, 2014)
Specifications of this paper are to discuss on the most traditions of the Prophet Muhammad pbuh about problematic social interactions of Moslems and Non-Moslems in the context of history and understanding which are implied inside it. The first is about greeting, congratulations for the great day. Secondly, Non-Moslems enter the mosque. The third is about eating meat of animals which are cut by Non-Moslems. All of these Specifications are often taking place with high intensity between Moslems and Non-Moslems in daily life. The problems of the relationship between Moslems and Non-Moslems are actual to be discussed. Â The issues are not infrequently to be in confinement the radical attitude of Moslems because of the understanding of religious texts, in this regard is the Quran, and hadith textually. The textually understandings of religious texts are combat command, killing, and dicriminating Non-Moslems. While, Non-Moslem communities do not try to learn on both the text histories from source Moslems deeply. Therefore, they have priori attitude towards certain clans. If they, especially for Moslems, are willing to learn aspects of religious texts comprehensively, so that, radical, and hostile attitude of Non-Moslem communities are nothing.Â  Â -----Spesifikasi tulisan ini membahas sebagian hadis-hadis Nabi Muhammad saw tentang problematika interaksi sosial Muslim dengan non Muslim dalam konteks sejarah dan pemahaman yang tersirat di dalamnya yang meliputi: pertama, seputar ucapan salam dan selamat hari besar; kedua, non Muslim masuk masjid ketiga, memakan sembelihan non Muslim. Ketiga interaksi ini sering terjadi dengan intensitas yang tinggi antara Muslim dengan non Muslim dalam kehidupan sehari-hari. Problematika hubungan antara Muslim dan non Muslim menjadi fenomena yang aktual. Tak jarang muncul sikap radikal dari kaum Muslim dalam memahami al-Qurâan dan hadis tentang perintah memerangi, membunuh dan mendiskreditkan non Muslim. Sementara di kalangan komunitas non Muslim muncul sikap apriori, karena tidak berusaha menilik lebih jauh teks dalam Alquan dan hadis tersebut. Â